Fish Diversity at Tanjung Luar Fish Landing Base (FLB) East Lombok as a Field Laboratory for Learning Biodiversity - Alpiansah, Hairul; Karnan, Karnan; Mahrus, Mahrus (Jurnal Biologi Tropis, 2024)
Fish is a vertebrate animal living in water, breathes with gills, and swims with fins. The research aims to find fish species and determine the fish species diversity index in FLB Tanjung Luar. The type of research carried out in this research is quantitative descriptive research. The study used a simple random sampling technique. The diversity of fish species in FLB Tanjung Luar has 64 families with 193 species from 12,470 individuals. Some of the fish species found were Euthynnus affinis, Decapterus russelli, Katsuwonus pelamis, Trichiurus lepturus, Rastrelliger kanagurta, Sardinella lemuru, Decapterus kurroides, Selaroides leptolepis, Sardinella gibbosa, Canthidermis maculata, Thunnus obesus, and Selar crumenophthalmus. Pelagic fish species are the most common in FLB Tanjung Luar with  10,724 individuals and  1746 demersal fish species found in FLB Tanjung Luar. The levels of diversity (H') and dominance (D) of fish in FLB Tanjung Luar are respectively 3.092 (high category) and 0.115 (low category).